2019
DOI: 10.1111/bjir.12474
|View full text |Cite
|
Sign up to set email alerts
|

Understanding What Has Been Happening to the Public‐Sector Pay Premium in Great Britain: A Distributional Approach Based on the Labour Force Survey

Abstract: This article investigates what has been happening to the public-sector wage differential in Great Britain over the period 1994-2017. The evidence indicates that apart from men in the lower part of the pay distribution, the public-sector pay premium has declined for all public-sector workers. This decline has coincided with a decline in the overall pay gap, which is associated with changes in the composition of public-and private-sector workforces. As the relative pay disadvantage experienced by public-sector w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The results showed that three of these characteristics, namely, work experience, income earners and dependents, have significant effect on pay satisfaction. In this regard, it is very rare to find empirical studies that tested the effect of these variables on pay satisfaction (Murphy et al , 2020). Therefore, the present study makes an important contribution for the literature on pay satisfaction and public sector.…”
Section: Discussion Of Findings With Implications For Theory and Prac...mentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that three of these characteristics, namely, work experience, income earners and dependents, have significant effect on pay satisfaction. In this regard, it is very rare to find empirical studies that tested the effect of these variables on pay satisfaction (Murphy et al , 2020). Therefore, the present study makes an important contribution for the literature on pay satisfaction and public sector.…”
Section: Discussion Of Findings With Implications For Theory and Prac...mentioning
confidence: 99%
“…governments can use its pay practices as a competitive strategy to attract competent individuals to the public sector (Murphy et al, 2020). Because of such competing interests of governments, the world has witnessed public-sector pay practices becoming increasingly formalized and sophisticated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Column 2 adds 11 industry dummies that identify the industry sector in which the workplace operates (Section level of the UK's Standard Industrial Classification (2007) ) and whether the workplace belongs to the private or public sector. These are intended to control for interindustry wage differentials and private/public sector pay differentials (Murphy et al ., 2020) which may be correlated with the gender composition of employment (and particularly the gender composition of management) (see Gannon et al ., 2007; Murphy et al ., 2020).…”
Section: Female Managers and The Gender Wage Gapmentioning
confidence: 99%